2010
DOI: 10.1111/j.1570-7458.2010.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 lessens predation of Chrysopa sinica on Aphis gossypii

Abstract: Most studies on the effects of elevated atmospheric CO 2 on organisms have focused on the performance of plants or herbivores. Few reports have examined the impact on the ability of predators at the third trophic level. In this experiment, we made use of open-top chambers to quantify the effects of elevated CO 2 on growth, development, and predatory ability of two successive generations of Chinese lacewing, Chrysopa sinica (Tjeder) (Neuroptera: Chrysopidae), feeding on cotton aphids, Aphis gossypii (Glover) (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Elevated CO 2 prolonged the development time of P. japonica but reduced larval and pupal durations of H. axyridis, C. sinica and L. japonica when preying on cotton aphids (Chen et al, 2005a;Gao et al, 2008). Moreover, elevated CO 2 increased aphid predation rate by H. axyridis, but reduced predation by C. sinica (Gao et al, 2010).…”
Section: Effects Of Elevated Co 2 On Natural Enemiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Elevated CO 2 prolonged the development time of P. japonica but reduced larval and pupal durations of H. axyridis, C. sinica and L. japonica when preying on cotton aphids (Chen et al, 2005a;Gao et al, 2008). Moreover, elevated CO 2 increased aphid predation rate by H. axyridis, but reduced predation by C. sinica (Gao et al, 2010).…”
Section: Effects Of Elevated Co 2 On Natural Enemiesmentioning
confidence: 94%
“…They mainly feed on cotton and wheat aphids, spider mites, eggs and young larvae of lepidopteran pests (Du et al, 2004). Moreover, elevated CO 2 increased aphid predation rate by H. axyridis, but reduced predation by C. sinica (Gao et al, 2010). Lysiphlebia japonica (Hymenoptera: Aphidiidae) is also a predominant parasitoid of cotton aphids in China and can effectively suppress the population of cotton aphids in early summer (Hou et al, 1997).…”
Section: Effects Of Elevated Co 2 On Natural Enemiesmentioning
confidence: 99%
“…The few studies have shown inconsistent performance. For instance, the harlequin ladybird Harmonia axyridis (Pallas) (Chen et al ) and parasitoid performance increased (Chen et al ; Sun et al ), whereas others have found decreased (Gao et al ; Gao et al ) or neutral responses (Wang ; Yin et al ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, studying the effects of increased atmospheric CO 2 on organisms has become an important subject of ecological research (Foss et al., ). Studies to date have mostly investigated the influence of elevated CO 2 on plants, phytophagous insects, and natural enemy insects (predators and parasitoids) (Lincoln et al., ; Bezemer & Jones, ; Gao et al, ; Wu et al., ; Chen et al., ; Mayor et al., ; Gao et al., ; Ge et al., ; Sun et al., , b; Xu et al., ; Mamatha et al., ; Meiyappan et al., ).…”
Section: Introductionmentioning
confidence: 99%